Comparison of thyroid scintigraphy and ARFI-elastography in autoimmune thyroid diseases - Sezgin, İlhan; Taşdemir, Bekir; Kilinc, Faruk; Hamidi, Cihad; Çoraplı, Mahmut (My University, 2022)
Aim: To compare the ARFI elastographic and scintigraphic quantitative data obtained from thyroid gland and to evaluate diagnostic value of ARFI elastographic measurements in autoimmune thyroid diseases. Material and Method: In the study a total of 61 patients (41 women, 20 men) including 24 Graves’ disease, 15 Hashimoto disease and 22 control subjects. The patients mean age was 33.9±10.9 years. Patients with thyroid nodules were not included in the study. Thyroid uptake was performed with Tc 99m pertechnetate and the elastosonography score of the thyroid gland was determined with ARFI. Findings of both disease groups were statistically compared with each other and control group Results: For thyroid uptake test; a statistically significant difference was found between two disease (p < 0.001) and between each disease and control group (p < 0.001 for Hashimoto, p <0.001 for Graves). However, for ARFI method; a statistically significant difference was not found between two disease (p=0.336) and between each disease and control group (p=0.14 for Hashimoto, p=0.08 for Graves). Conclusion: Thyroid scan and thyroid uptake measurements are extremely valuable in differential diagnosis of autoimmune thyroid diseases and ARFI elastosonographic measurements don’t seem to replace scintigraphic datas.
Keywords: ARFI; Thyroid scintigraphy; thyroid uptake; Graves’ disease; Hashimoto's thyroiditis